Elevating Guest Experience: Enhancing Order Taker Services At The Sunan Hotel - Muhamad Dafillin; Tuwuh Adhistyo Wijoyo (PT. Banjarese Pacific Indonesia, 2024)
The study aims to gain a better understanding of the role of Order Taker in improving the quality of Housekeeping services at the The Sunan Hotel. In addition, the study also tries to identify problems faced by staff and ways to address them. The research was designed using a descriptive qualitative approach. The theory used is the quality of service. The data obtained was collected through interviews, observations, and literary studies. The result of this research is that Order Taker helps improve the quality of Housekeeping services by receiving and processing guest requests in a timely and efficient manner. Handle guest complaints in a friendly and professional manner. Give me a polite and friendly service. Create a positive relationship with the guests. Using technology to be more efficient. Maintain the comfort and hygiene of the guest room. The obstacles faced are the Order Taker facing many challenges, including high work pressure, lack of technological support, incompatibility with Housekeeping staff, and lack of training and motivation. As for the strategy used to tackle this problem is to keep up with trends using technology, manage workloads, and improve communication. Team coordination, training, and incentives.